Influence of Poverty on Economic Growth in Sub-Saharan Africa, the Role of Financial Stability - Lambon, Justice Iddrisu; Ocansey, Evans Osborn Nene Daker; Ababio, Opoku Kwaku (Archives of Business Research, 2025)
The primary objective of the study is to assess whether and how financial stability alters the relationship between poverty and economic growth in SSA. To achieve this, the study employs a quantitative panel data approach, analyzing data from 38 SSA countries over the period 2000–2023. Using the Difference Generalized Method of Moments (GMM) estimation technique, the analysis accounts for endogeneity, unobserved heterogeneity, and dynamic effects. The findings reveal that poverty has a significant negative effect on economic growth, while the interaction between poverty and financial stability is also negative and statistically significant, suggesting that financial instability amplifies the adverse effects of poverty on growth. Notably, financial stability on its own is not a statistically significant predictor of growth, highlighting the complexity of its role in development contexts. These results have important implications for policymakers and researchers. They underscore the need for financial sector reforms that prioritize inclusion and resilience as preconditions for effective poverty reduction strategies. The study also contributes to accounting and development finance research by emphasizing the relevance of financial system transparency and accountability in fostering inclusive economic development.